Molecularly imprinted polymers for protome analysis - Bonini, Francesca (Cranfield University, 2008)
Fast and efficient methods for the detection of insurgence and progression of diseases are at the basis of modern diagnostics and medicine. In this concern, biomarkers represent a powerful diagnostic tool, as their expression profiles well correlate with the pathology progression. Thus, the pathological state could be diagnosed by measuring the altered presence of a biomarker. In this direction, conspicuous help has been given by proteomics, intended as the study of the protein pattern of a sample and most frequently performed by two-dimensional electrophoresis. Although the proteome approach is a powerful analytical method, its application to biological samples for the detection and quantification of putative biomarkers is hampered by technical problems, in fact, the wide diversity in concentrations exhibited by the proteins present in the biological samples, with a concentration range spanning over nine orders of magnitude, and the relative abundance of each protein, are responsible of masking the less abundant species and of their loss in traceability. The aim of my PhD project is to apply Molecularly Imprinted Technology to the specific removal of a high abundance protein (Human Serum Albumin, HSA) frequently affecting proteomic analysis, in order to increase the detection of potential biomarkers. This technology allows the creation of artificial recognition sites in synthetic polymers for a specific protein. These sites are tailor-made in situ by co-polymerisation of functional monomers and cross-linkers around the template molecules. Two different approaches have been assayed in order to remove HSA: • Immobilisation of protein template on a rigid silica support (bead) and creation of polymer around beads. • Polymerisation in bulk of a polymer with protein template and application of this polymer to multicompartment electrolyser. In both of the cases, the chemical and structural features of the polymers have been analysed, after that they have been applied to complex proteome pre-treatment, obtaining encouraging results.